2020
DOI: 10.4103/ijcm.ijcm_357_19
|View full text |Cite
|
Sign up to set email alerts
|

Risky riding and its correlates in two-wheeler riding young men: Pillion riders' perspective

Abstract: Background: Risky riding is one of the major contributing factors in road fatalities. The present study aimed to explore the risky riding behaviors and its correlates in two-wheeler riding young men, as ascertained from pillion riders' perspective. Materials and Methods: A survey that captured perspective of pillion riders about two-wheeler riding young men with whom they used to pillion ride most frequently was administered on 115 subjects. The survey consisted of item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…This could be correlated with the highest percentage of two-wheeler riders as victims with their non-usage of safety head gears like helmets. 14 Chhetri TB et al 8 in their study observed that head trauma was the most affected region with 73.3% cases which is in conjunction with the present study. Similar findings were observed in a study conducted by Hassan NA & Emara A 15 where the highest number of injuries are sustained in the lower limb (37.26%) closely followed by head injury (23.84%).…”
Section: Discussionsupporting
confidence: 89%
“…This could be correlated with the highest percentage of two-wheeler riders as victims with their non-usage of safety head gears like helmets. 14 Chhetri TB et al 8 in their study observed that head trauma was the most affected region with 73.3% cases which is in conjunction with the present study. Similar findings were observed in a study conducted by Hassan NA & Emara A 15 where the highest number of injuries are sustained in the lower limb (37.26%) closely followed by head injury (23.84%).…”
Section: Discussionsupporting
confidence: 89%